A NEW TWO-PARAMETER LIFETIME DISTRIBUTION WITH APPLICATION (FUDMA JOURNAL OF SCIENCES, 2020)
There are several methods to combine and extend the continuous lifetime models to increase their flexibility and generality. Here we proposed a new lifetime distribution model with two parameters. Various lifetime distribution representations related to this model are derived and presented with their properties. Several Statistical measures and their properties are also studied. The method maximum likelihood estimator is discussed. Simulation studies are performed to assess the finite sample performance of the maximum likelihood estimators (MLEs) of the parameters. In the end, to show the flexibility of this distribution, an application using real data sets is presented
Keywords: Log-logistic distribution; Hazard function; Maximum likelihood estimation; Simulation.